Is there a role for elective neck dissection with salvage laryngectomy? A decision‐analysis model. (17th May 2013) - Hilly, Ohad; Stern, Sagit; Horowitz, Einav; Leshno, Moshe; Feinmesser, Raphael
Abstract : Objectives/Hypothesis: Elective neck dissection for the clinically negative neck is often a matter of debate. A decision‐analysis model that was published in 1994 established the widely accepted principle that neck dissection is warranted when the risk for occult metastases is higher than 20%. The aim of the present study was to build a specific and up‐to‐date decision‐analysis model to determine the need for elective neck dissection during salvage laryngectomy after chemoradiation failure and to identify the variables that effect the decision. Study Design: Decision‐analysis model. Methods: A decision‐analysis model was performed to compare the outcome of patients after salvage total laryngectomy with and without an elective neck dissection. Probabilities and expected utilities were derived from available literature to construct the model. Monte Carlo simulation and sensitivity analysis were used to calculate our models' outcomes and to identify the variables that influence the model most, respectively. Results: When calculating our model results with published data, we found that elective neck dissection is not warranted during salvage total laryngectomy. Optimal decision was found to be sensitive by two variables: 1) the probability for cure with neck dissection, and 2) the probability for regional‐only recurrence after salvage laryngectomy without neck dissection. In multiway sensitivity analysis, only when cure rate with neck dissection exceeded 82%, adding neck dissection was the preferred decision. In practice, cure rates for patients after salvage total laryngectomy are around 50% to 65%. Conclusions: Based on our decision‐analysis model, we do not recommend routine elective neck dissection during salvage total laryngectomy after failure of chemoradiation. Level of Evidence: NA. Laryngoscope, 123:2706–2711, 2013